2017
DOI: 10.17957/ijab/15.0264
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency Micropropagation of Dormant Buds in Spine Base of Red Pitaya (Hylocereus polyrhizus) for Industrial Breeding

Abstract: By the systematical optimization on explants sterilizing, induction and multiplication of adventitious shoots, rooting and seedling transplanting, the high-efficient regeneration system and domestication transplanting technology for red pitaya (Hylocereus polyrhizus) were established using dormant buds in spine base as primary materials. Results showed that the optimal surface sterilization procedure of red pitaya explants (nodal segments with one spine base) was 0.2% mercuric chloride (HgCl 2 ) treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…When leaves of O. Fragrance were under high temperature stress, ADH gene expression would be increased because of the resistance response mechanism activation in order to avoid from heat damage. Many researches about functional components in the leaves, flowers (Ge et al, 2018a and2018b), barks (Ge et al, 2017a and, stems (Ge et al, 2017c and2017d), roots (Ge et al, 2017e;, fruits (Jiang et al, 2018a and2018b), timbers (Peng et al, 2017a and and byproducts (Liu et al, 2017;Xie et al, 2018) of plants showed that they contain many bioactive components (Peng et al, 2016;He et al, 2017;Cheng et al, 2017;Yang et al, 2017;Qin et al, 2017;Xu et al, 2018;Wang et al, 2018). This result was consistent with the resistance response function of ADH (Strommer et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…When leaves of O. Fragrance were under high temperature stress, ADH gene expression would be increased because of the resistance response mechanism activation in order to avoid from heat damage. Many researches about functional components in the leaves, flowers (Ge et al, 2018a and2018b), barks (Ge et al, 2017a and, stems (Ge et al, 2017c and2017d), roots (Ge et al, 2017e;, fruits (Jiang et al, 2018a and2018b), timbers (Peng et al, 2017a and and byproducts (Liu et al, 2017;Xie et al, 2018) of plants showed that they contain many bioactive components (Peng et al, 2016;He et al, 2017;Cheng et al, 2017;Yang et al, 2017;Qin et al, 2017;Xu et al, 2018;Wang et al, 2018). This result was consistent with the resistance response function of ADH (Strommer et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…2-Cyclopenten-1-one, 2-hydroxy-3-methyl- (1.67%) are used as flavoring and sweetener synergistic agents. They are mainly used to make smoke, cream, hard candy and apricot essence (Qin et al, 2017). 2-Methoxy-4-vinylphenol (1.38%) and Penol, 2,6-dimethoxy-(1.46%) can be used in the food additive and spices industry.…”
Section: Resultsmentioning
confidence: 99%
“…Bozkurt et al [ 187 ] reported maximum shoot proliferation with 4.0 mg/L 6-BA and rooting with 1 mg/L IBA. Qin et al [ 188 ] showed 5.5 mg/L 6-BA and 0.1 mg/L NAA, while in a recent study by Lee and Chang [ 189 ], 0.20 mg/L NAA, 200 mg/L activated charcoal and 1.0 mg/L 6-BA were the best media for shooting H. polyrhizus . Hua et al [ 190 ] achieved a maximum number of shoots per explant with 3.0 µM ZT and 0.5 µM IBA, while the best shoot propagation media were 13.68 µM ZT and 2.46 µM IBA.…”
Section: Propagation Micropropagation Cell and Tissue Culturementioning
confidence: 99%
“…Half-strength MS media with 0.5 mg/L NAA and 0.3 mg/L IBA [ 188 ] induce precocious rooting; however, if IBA is used in the shoot proliferation media, then maintaining shoots for 6–7 weeks on the media also allows rooting [ 97 ]. Plants that reach 2.5 cm in height are hardened in bottles for 4–5 d; roots are cleaned from agar using tap water, rinsed for 10 min in 10% ( v / v ) fungicide [ 188 ], and transplanted in plastic pots with autoclaved 1:1 perlite:soil. Orea and Medrano [ 192 ] suggested the use of tezontle and perlite mediums for good acclimatization and rooting.…”
Section: Propagation Micropropagation Cell and Tissue Culturementioning
confidence: 99%